Mothers' Knowledge and Practice towards the Effects of Iron Supplementation on Tooth Staining and Dental Caries in Yazd, Iran - iman parisay; Sara Arastoo; Aliasghar Soleymani; Alaleh Toloee; Mahsa Ahmadi Shadmehri (Mashhad University of Medical Sciences, 2020)
Aims: Iron supplementation in children under 5 years of age is recommended on the basis of anaemia prevention. This study aims to assess the mother's knowledge and practice towards the effects of iron supplementation on dental caries and staining in children aged 6 months to 2 years in Yazd, Iran. Methods: A randomized cross-sectional study was conducted on 403 mothers of children (aged 6 months to 2 years) who referred to healthcare centers in Yazd during 2011. The mothers' knowledge and practice levels were assessed using a questionnaire, and the results were categorized into sufficient or insufficient. The Chi-square test was used to analyze the data. Results: According to the results, 241 (59.8%), and 273 (67.7%) mothers obtained sufficient levels of knowledge, and practice, respectively. Moreover, mothers' educational levels had a statistically significant relationship with their knowledge regarding iron supplementation (P<0.001). Additionally, the mother's practice toward iron supplementation correlated significantly with mothers' educational level (P<0.001) and occupational status (P=0.018), as well as the birth order of the child (P<0.001). Conclusion: More than half of the mothers had sufficient knowledge and practice towards the effects of iron supplementation on dental caries and staining